Nočni bojevniki - Šmitek, Zmago (Studia mythologica Slavica, 2014)
The author discusses records of the documents of two inquisition processes from the years 1583 and 1596 against a Friulian miller who was condemned as a member of the sect of banandanti , discovered by Italian historian Carlo Ginzburg and published in his famous book Cheese and Worms (1976). The Benandanti claimed that they were secretly gathering "in spirit" and fighting four times a year with sorcerers and witches in night battles. He compares them with Slovenian oral tradition about the kresniki and their opponents, the vedomci.
Keywords: mitologija; mythology; beliefs; verovanja; witchcraft; čarovništvo; Slovenia; Slovenija; Friuli–Venezia Giulia; Furlanija